A study of the importance of personal financial planning among employees; case study; Metro Kajang Holdings Berhad / Nurashikin Muhamad Shukor - Shukor, Nurashikin Muhamad (Faculty of Business and Management, 2011)
Personal Finance Planning can also be defined as the method by which people anticipate and plot their future actions to reach their goals. When one engages in financial planning, it is usually to solve a problem or to structure a plan for the future. This study explores the attitude of individual in financial knowledge and financial consciousness towards personal finance planning. This study was conducted at Metro Kajang Holdings Berhad and there are two independent variables involved that are financial knowledge and financial consciousness. Data collected and evidences are being processed by using the SPSS Computer program. Researcher also wants to test the hypothesis formulated earlier by using the multiple regression analysis. Pearson’s Correlation Coefficient was used in order to know the relationship between independent variables (financial knowledge and financial consciousness) and dependent variables (attitude towards personal financial planning). From the finding, most of employees are aware about the importance of personal finance planning but less of them apply the knowledge in their daily life which result to a less consciousness towards personal finance planning. For recommendation, organization could increase awareness through campaign within the company for the sake of employees’ well-being. An awareness program can increase the understanding of financial planning and also create link between individual action and behavior towards financial planning. It is crucial for individual to understand the knowledge they have about personal finance planning so they are conscious about the implication of their incapability to understand the importance of personal finance planning.